Amulet: Prince of the Elves Book 5 - Kibuishi, Kazu 1978- (New York : Graphix, 2008)
After chasing the monster that kidnapped their mother, Emily and Navin find themselves in a magical world of man-eating demons and shadowy enemies, where they must learn to control an amulet given to them by their grandfather.
bk. 1. The stonekeeper -- bk. 2. The stonekeeper's curse -- bk. 3. The cloud searchers -- bk. 4. The last council -- bk. 5. Prince of the elves
Keywords: Siblings -- Fiction; Charms -- Fiction; Fantasy fiction